ASSOCIATION BETWEEN CHRONIC APICAL PERIODONTITIS AND OXIDATIVE STRESS OR META-INFLAMMATION: A CROSS-SECTIONAL OBSERVATIONAL STUDY - Antonia Boca; Ada Delean; Sanda Ileana Cîmpean; Adina Bianca Boșca; Cosmina Ioana Bondor; Sebastian Candrea; SALIVAGES Project group; Aranka Ilea (Romanian Journal of Oral Rehabilitation)
Dental pulp inflammation culminates in gangrene, often progressing to chronic apical periodontitis (CAP), thus representing a potential source of inflammatory factors with an impact on overall general health. This study investigated the impact of periapical lesions on patients’ general homeostazis and systemic inflammatory status. Two hundred patients were enrolled in a cross-sectional observational study, with 73 diagnosed with periapical inflammation based on orthopantomography and clinical assessment. The following parameters were recorded from peripheric blood and saliva samples: total blood count, total lipids, plasma inflammatory factors (hsCRP), markers of nitro-oxidative stress (total antioxidant capacity), carbohydrate metabolism and advanced glycation end-products (carboxymethyllysine). Patients were divided into two groups based on the number of dental units affected by CAP relative to the remaining teeth: group 1 (less than the median number of dental units affected by CAP) and group 2 (equal or higher than median number of dental units affected by CAP). Plasma levels of fructollysine, total antioxidant capacity, and salivary levels of thiols were significantly higher in Group 2. Conversely, plasma and salivary levels of pyrraline, along with salivary oxidative stress index were significantly lower in Group 2. Salivary arginine values were slightly lower in Group 2. Within the limitations of the present study, we can conclude that CAP appears to have a minor influence on meta-inflammation and inflammatory status. However, its cumulative effect with other associated pathologies could impact the overall modulation of the inflammatory response and general homeostasis. Further research is needed to confirm these findings.